Mangiferin promotes osteogenic differentiation and alleviates osteoporosis in the ovariectomized mouse via the AXL/ERK5 pathway - Jinwen He; Xingwen Wang; Dacheng Zhao; Bin Geng; Yayi Xia (Frontiers Media S.A., 2022)
Mangiferin is a xanthone glucoside extracted from multiple plants, which has been shown to inhibit bone resorption and alleviate osteoporosis. However, the effect of purified Mangiferin on osteoporosis and its specific mechanisms is unknown. This study aimed to explore whether Mangiferin can promote osteogenic differentiation and alleviate osteoporosis in ovariectomized (OVX) mice and explore the potential mechanisms. Different concentrations and durations of Mangiferin were applied to MC3T3-E1 cells. The optimal concentration and duration of Mangiferin were determined by evaluating the cell viability via cell count kit-8 (CCK-8). The gene and protein expressions of AXL, ERK5, and osteogenic differentiation markers, including BMP2, Collagen1, OPN, Osterix, and Runx2, were detected using western blotting, qRT-PCR, immunofluorescence, and flow cytometry. Mangiferin was administered to OVX mice, and the severity of osteoporosis was evaluated by H and E staining, immunohistochemistry (IHC), microscopic computed-tomography (micro-CT) scanning, western blotting, and immunofluorescence of bone tissue. We found that Mangiferin promoted osteogenic differentiation in a dose-dependent manner at concentrations less than 30 μM. The 30 μM Mangiferin significantly upregulated the expression of AXL, ERK5, and osteogenic differentiation, including the ALP activity, percentage of alizarin red, and the levels of osteogenic differentiation markers. However, these expression levels decreased when AXL was knocked down in MC3T3-E1 cells and it could not be rescued by Mangiferin. Mangiferin relieved osteoporosis in OVX mice without causing severe organ damage. This study concluded that Mangiferin promoted osteogenic differentiation of MC3T3-E1 cells and alleviated osteoporosis in OVX mice. The potential mechanism was via the AXL/ERK5 pathway.